Recent climate change in western black sea region of Turkey by paleoclimatic reconstruction of borehole temperatures - ERKAN, KAMİL; TAYANÇ, METE; AKKOYUNLU, BÜLENT OKTAY (My University, 2023)
The impact of recent climate change varies around the world, and understanding the regional variations is important for making accurate deductions and generating future climate predictions and mitigation plans. Borehole temperature reconstruction is one of the common methods to determine the ground surface temperature (GST) history of a region. In this study, high-precision (< 0.01 K) borehole temperature-depth data from five different locations in Western Black Sea Region of Turkey were used for reconstruction of the GST changes for the last century. Four of the measurement sites are located in rural areas in the inland section and free from the urban heat island interference. The reconstructions reveal that GSTs have dropped by an average of 0.1 °C between 1900 and 1970 and have risen by an average of 0.99 °C between 1970 and 2010 in the study area. Results from inland sites show average cooling of 0.24 °C between 1900 and 1975 and average warming of 0.94 °C until 2010. The results in the coastal area show no cooling period. The rapid warming trend in 1990–2010 revealed by GST reconstructions indicates high sensitivity of the region to present-day global warming.
Keywords: Jeofizik Mühendisliği; Mühendislik ve Teknoloji; Geophysical Engineering; Engineering and Technology; Temel Bilimler (SCI); Yerbilimleri; JEOKİMYA VE JEOFİZİK; Natural Sciences (SCI); GEOSCIENCES; GEOCHEMISTRY & GEOPHYSICS; Jeofizik; Fizik Bilimleri; Jeokimya ve Petroloji; Geophysics; Physical Sciences; Geochemistry and Petrology; Black Sea region; borehole temperatures; Climate change; paleoclimate; Turkey